The Influence of Brand Image, Price, and Service Quality on Customer Loyalty Through Customer Satisfaction - Paula Sumarandak; Ronny H. Walean (Jurnal Economic Resource, 2026)
This study aims to examine the influence of brand image, price, and service quality on customer loyalty at Bakery UNKLAB, with customer satisfaction as a mediating variable. The research focuses on the Indonesian market context, employing a quantitative survey and collecting data from 216 Bakery UNKLAB customers. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test the hypothesized relationships. The findings reveal that brand image, price, and service quality significantly contribute to customer satisfaction, which in turn strongly and positively affects customer loyalty. Customer satisfaction also serves as a crucial mediator linking these marketing factors to loyalty. These results offer valuable strategic insights for Bakery UNKLAB management in designing marketing policies that emphasize enhancing satisfaction to strengthen consumer loyalty in a competitive market.